Womens' Role in Household Decision Making in Newari Community - Malakar, Indra (Cognition, 2019)
This study attempts to explore women's role in household decision making in Newari community among married women of 15-60 years of Kirtipur Municipality 5, Kathmandu district. This study has used both quantitative and qualitative data for the study purpose and also includes few case studies for the qualitative purpose. Mean age of the respondent was 38.52 (±8.72). Total respondents of this study were 125 married Newari women. The study is based on primary data collection in terms of decision making about their marriage, selling and buying of assets, daily consumption of food, educational enrollment of kids and using family income. This study reveals that Newari married women have effective role in decision making on marriage and educational enrollment of their kids however their participation is quite low in decision making for daily consuming food and selling and buying of assets.